Analysis of Junior High School Students' Scientific Literacy Using the Rasch Model - Mutiara Nurul Lita Azizah; Sri Ngabekti; Sigit Saptono; Endang Susilaningsih (International Conference on Science, Education, and Technology, 2023)
This study aims to analyze the essay test instrument with 11 questions using the Rasch model to measure scientific literacy skills in the matter of Substances, Forms of Substances, and Their Changes. This research is a type of quantitative descriptive research. The research subjects were 84 class VII students at SMP PGRI 1 Ajibarang. The research data were analyzed using the winstep program to obtain a logit value. From the output of the Winsteps program, the results obtained were 9 questions according to the Rasch model with an average ± average Outfit MNSQ for person and item ± 0.98 and 0.98 respectively. Meanwhile, the Outfit ZSTD values for persons and items are ± 0 and -0.01, respectively. While the reliability of the instrument expressed in Cronbach's alpha is 0.95.